JUSTIFICATION OF VALUES FACTOR CONTROLLER VIBRATION DAMPING SHIPPING BRIDGE CRANES - M. S. Korytov (Вестник СибАДИ, 2017)
As a result of computational experiments on the simulation model of the bridge crane with controller cancellations load fluctuations when it is moved to test trajectories are obtained depending on the indicators characterizing the process of moving from the regulator coefficients. The indicators used by the maximum absolute error of the linear referencing load, the maximum speed of movement of the bridge crane and a cargo truck, the maximum acceleration of the bridge and trolley. Substantiated rational values of the vibration damping control factors, which do not appear self-sustaining self-oscillation of the bridge and trolley.